Therapeutic toy in nursing care in inhalation therapy with children: experience of mothers - Contim, Divanice (2023)
Objective: to describe mothers' experiences regarding the use of therapeutic toys on their children during nursing care in inhalation therapy. Methods: descriptive, exploratory and qualitative analysis study, developed in an emergency care unit. Mothers who accompanied their children during inhalation therapy participated. Data collection took place between October 2018 and March 2019, through semi-structured interviews. The data was interpreted through Thematic Content Analysis. Results: 23 mothers participated, aged between 22 and 44 years old, 54% had a civil union with the child's father, 40% had completed secondary education, 55% were homemakers and 60% had a family income of one minimum wage. Two thematic categories were created: “Toys as a relief from the tension caused by the procedure” and “Toys as a strategy for improving care”. Conclusion: the use of therapeutic toys from the mothers' perspective contributed to the treatment of their children, as they became calmer and safer when undergoing inhalation therapy.